The E3 Ubiquitin Ligase c‐Cbl Inhibits Microglia‐Mediated CNS Inflammation by Regulating PI3K/Akt/NF‐κB Pathway - Dong, Lin (CNS Neurosci Ther, 2016)
BACKGROUND: Microglia‐mediated inflammation may play an important role in the pathophysiology progression of neurodegenerative diseases, such as Parkinson's disease (PD), but the molecular mechanisms are poorly understood. AIMS: This study sought to determine whether E3 ubiquitin ligase c‐Cbl plays a role in the brain inflammation and to explore the relevant molecular mechanism. METHODS: After BV2 microglial cells and c‐Cbl‐deficient mice were treated with lipopolysaccharide (LPS), neuroinflammation and microglial activation were evaluated by immunohistochemistry, ELISA and Western blot. We further investigated the possible mechanism of c‐Cbl in regulating microglial activation. RESULTS: Here, we showed that the E3 ubiquitin ligase c‐Cbl had high expression in brain tissues including substantia nigra pars compacta (SNc), striatum and hippocampus, and it was abundantly expressed in microglia. Systemic LPS administration resulted in more severe microglial activation in CNS and increased expression of brain proinflammatory factors (TNF‐α, IL‐6, IL‐1β and MCP‐1) in c‐Cbl knockout mice than wild type mice (WT). Downregulation of c‐Cbl expression with c‐Cbl siRNA in BV‐2 microglial cells demonstrated a more robust increase in the proinflammatory factors release and NF‐κB p65 nuclear translocation than that in control siRNA. Interestingly, Akt phosphorylation induced by LPS was also significantly augmented after c‐Cbl knockdown. Moreover, blockade of PI3K/Akt activation by LY294002 significantly reduced inflammation response and NF‐κB p65 nuclear translocation. CONCLUSION: In sum, c‐Cbl inhibits expression of LPS‐stimulated proinflammatory cytokines and chemokines in microglia. We demonstrate an unprecedented role for c‐Cbl in microglia‐mediated neuroinflammation involving PI3K/Akt/NF‐κB pathway.